Correction: Xie et al. Exploring the Mechanisms and Preventive Strategies for the Progression from Idiopathic Pulmonary Fibrosis to Lung Cancer: Insights from Transcriptomics and Genetic Factors. Biomedicines 2024, 12, 2382 - Kai Xie; Xiaoyan Tan; Zhe Chen; Yu Yao; Jing Luo; Haitao Ma; Yu Feng; Wei Jiang (Biomedicines)
In the original publication, there was a mistake in Figure 11 as published [...]